2016
DOI: 10.7567/jjap.55.06jf02
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study for lifetime distribution of middle-of-line time-dependent dielectric breakdown affected by global and local spacing variations

Abstract: The impact of process fluctuations for the lifetime distribution of middle-of-line time-dependent dielectric breakdown was investigated by Monte-Carlo simulation. Global and local variations were simulated using a doubly truncated normal distribution. A goodness of fit to the generated data was determined statistically in terms of the Weibull distribution and clustering model. A change in the standard deviation of the global variation shows a large contribution to lifetime variation. However, it does not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In this case, the probability plot shows a convex upward shape. [9][10][11][12][13][14][15][16][17][18] In the semiconductor reliability domain, as mentioned above, the Weibull distribution is assumed for dielectric breakdown with a temporospatial homogeneousness. Particularly, the weakest link concept will correspond to the TDDB lifetime.…”
Section: Break Of the Uniformity Assumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the probability plot shows a convex upward shape. [9][10][11][12][13][14][15][16][17][18] In the semiconductor reliability domain, as mentioned above, the Weibull distribution is assumed for dielectric breakdown with a temporospatial homogeneousness. Particularly, the weakest link concept will correspond to the TDDB lifetime.…”
Section: Break Of the Uniformity Assumptionmentioning
confidence: 99%
“…The applications of a TDC model that describes the non-Poisson characteristics of a lifetime applied to TDDB are introduced. The physical and statistical background of the modeling and the mathematical methods for the accurate parameter extraction [14][15][16][17][18] are introduced. These elements provide methods to analyze and evaluate the TDDB characteristics affected by complicated defect densities.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al had reported their progressive research about this concept. [8][9][10][11] The lifetime distribution function, which is proposed as the time-dependent clustering (TDC) model, has two shape parameters as follows: [8][9][10][11][12]27,28)…”
Section: Introductionmentioning
confidence: 99%
“…3,4,[25][26][27][28][29] The model has two shape parameters and is called the generalized Burr-type XII (GBXII) distribution in statistics. 30,31) The cumulative probability function of the lifetime distribution with defect clustering is described by the BXII distribution as…”
Section: Distribution Functionmentioning
confidence: 99%
“…A complicated shape of the TDDB lifetime distribution 3,4,[25][26][27][28][29] is represented by both the intrinsic variation of TDDB and the physical variation of acceleration stress. Therefore, large-scale observation of lifetime is required for evaluating the lifetime distribution of TDDB affected by the clustering defect.…”
Section: Introductionmentioning
confidence: 99%